The coffee rails: a historical and socioeconomic analysis in the western region of Sao Paulo state - Dias, Karina Tonelli Silveira; Lima, Fabiana da Silva; Mazzutti, Fernando Mauro de Toledo Piza da Costa; Silva, Allan Leon Casemiro; Lourenzani, Wagner Luiz [UNESP]; Bernardo, Cristiane Hengler Correa [UNESP] (Univ Cruz Alta, 2018)
This paper aims to analyzing the coffee expansion to the emergence of railroads in the western region of Sao Paulo state, particularly in the regions of Alta Paulista and Alta Sorocabana, addressing historical and socioeconomic aspects. For that, an exploratory, bibliographical and documentary research of qualitative nature was realized. It was identified that the emergence of railroads was strongly influenced and directed to the flow of coffee, which was the main economic activity of the time. This factor allowed the entry in the Sao Paulo state and, consequently, the formation of villages that would later originate the cities. The urbanization of the western region of Sao Paulo state occurred with the demand for labor, national and immigrant, in the coffee mills and for the construction of railroad tracks, so much that many cities were originated on the edge of these. It is concluded that the trinomial coffee culture, railway expansion and population growth were essential to the growth, expansion and development of the state of Sao Paulo, mainly in the Western region.
Keywords: Coffee Expansion; Railroads Expansion; Urbanization